Divergent ring-opening coupling between cyclopropanols and alkynes under cobalt catalysis - Yang, Junfeng (2018)
Cobalt–diphosphine catalysts promote ring-opening coupling reactions between cyclopropanols and unactivated internal alkynes, affording either β-alkenyl ketones or multisubstituted cyclopentenol derivatives in good yields with good to excellent regioselectivities. The chemoselectivity between these β-alkenylation and [3 + 2] annulation reactions, which likely share a cobalt homoenolate as a key catalytic intermediate, is exquisitely controlled by the reaction conditions, with the solvent being a major controlling factor. The reactions are proposed to involve ring opening of cobalt cyclopropoxide into homoenolate, migratory insertion of the alkyne into the Co–C bond, and protodemetalation or intramolecular carbonyl addition of the resulting alkenylcobalt species. The feasibility of these reaction steps was supported by DFT calculations.